STRATEGI BERTAHAN PEDAGANG KAKI LIMA KULINER DI ERA DIGITALISASI: STUDI KASUS ANGKRINGAN DI BAWEN KABUPATEN SEMARANG - Berkat Junius Gea; Henry Yuliamir (LPSDI Bina Patria, 2022)
Street vendors (PKL) play an important role in the people’s economy, including in Bawen District, Semarang Regency, where angkringan has become a cultural and culinary icon. However, the development of digitalization through social media, online food delivery platforms, and digital payment systems presents both challenges and opportunities for these traditional vendors. This study aims to analyze the survival strategies of angkringan vendors in facing digitalization, identify supporting and inhibiting factors, and assess the role of digitalization in enhancing business competitiveness. This research employs a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles & Huberman’s model (data reduction, data display, and conclusion drawing). The findings reveal that the vendors’ survival strategies include product innovation, utilization of digital technology, and strengthening social networks. Supporting factors for digital adaptation include wider internet access, government support through QRIS, and younger consumers accustomed to technology. Inhibiting factors consist of low digital literacy, limited capital, and concerns about transaction security. Digitalization has been proven to improve competitiveness by expanding markets and facilitating transactions, although the adoption level remains uneven. These findings highlight the importance of an inclusive digital ecosystem to support the sustainability of the informal sector